PUBLIC PERCEPTION OF AMIL ZAKAT INSTITUTIONS IN INDONESIA: INSIGHT DISCOVERY FROM MACHINE LEARNING - Timur, Yan Putra; Ratnasari, Ririn Tri; Pitchay, Anwar Allah; Jamilu, Usman (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
This study aims to identify the most popular topics and words in conversations on Twitter with the topic of Amil Zakat in Indonesia. This research also aims to identify the sentiments and emotions of netizens about the Amil Zakat in Indonesia. This study uses a qualitative method with a sentiment analysis approach with the help of Orange Data Mining. The data used are tweets from Twitter taken from 16 to 23 April 2023. Researchers used the keywords "Amil Zakat" "Lembaga Zakat" and "Lembaga Amil Zakat" to get a total of 1,000 tweets. The results of the study show that the words "Zakat" "Badan" and "Nasional" are the three words that appear most often in discussions of Amil Zakat institutions on Twitter. These three words refer to the BAZNAS, where based on the metadata processed in this study, many people, individuals, and institutions distribute their zakat through BAZNAS. Overall, Twitter is dominated by tweets with neutral sentiments, shown by happy emotions, as much as 93.51% of the total tweets. Amil Zakat can increase the intensity of communication through social media especially regarding solicitations for the community, as well as achieving the collection and distribution of zakat funds as a form of information disclosure to the public